1990
DOI: 10.3109/02688699008992741
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent lumbar disc protrusion

Abstract: Seventy-six patients who underwent re-operation for recurrent lumbar disc protrusion were analysed to define the pattern of disc recurrence and the outcome following the operation. Whereas recurrence after an L4/5 discectomy occurred at the same level in 66%, recurrence after an L5/S1 discectomy was as likely to occur at L4/5 as at L5/S1. Outcome was inversely related to the number of operations. A satisfactory outcome after the first procedure was usually associated with a satisfactory ultimate outcome. Assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
4

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 5 publications
1
46
1
4
Order By: Relevance
“…Previous reports have indicated that patients undergoing a primary discectomy have a 76%-95% chance of satisfactory results as measured by pain and functional measures, whereas only 59%-81% of those undergoing a revision discectomy will achieve the same results. 6,15,18,21,23 Although our findings suggest that QOL improvements are less for those undergoing revision discectomy than for those undergoing primary discectomy, the improvements experienced by revision discectomy patients nonetheless often exceed the MCID threshold. In contrast, QOL outcomes tend to be relatively poor for patients who experience another recurrent (third) herniation after revision discectomy.…”
Section: Discussioncontrasting
confidence: 40%
“…Previous reports have indicated that patients undergoing a primary discectomy have a 76%-95% chance of satisfactory results as measured by pain and functional measures, whereas only 59%-81% of those undergoing a revision discectomy will achieve the same results. 6,15,18,21,23 Although our findings suggest that QOL improvements are less for those undergoing revision discectomy than for those undergoing primary discectomy, the improvements experienced by revision discectomy patients nonetheless often exceed the MCID threshold. In contrast, QOL outcomes tend to be relatively poor for patients who experience another recurrent (third) herniation after revision discectomy.…”
Section: Discussioncontrasting
confidence: 40%
“…PLID can recur at the same disc and side as the primary PLID 10,13 or at the same disc and contralateral side or at a new disc at different level. 9,13 Annular incision performed at primary discectomy may be a predisposing factor for recurrence, and the presence of scar tissue may affect the results of revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…9,13 Annular incision performed at primary discectomy may be a predisposing factor for recurrence, and the presence of scar tissue may affect the results of revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…High reoperation rates have been reported in the literature, and several studies have shown inferior outcomes for patients who undergo reoperation 7,12,18,21,22 . This investigation focused on improving clinicians' understanding of risks and outcomes when indicating IDH patients for surgery, thus improving long-term outcomes and minimizing unnecessary costs and morbidity associated with multiple operations.…”
Section: Risk Factors F O R Reoperation I N Pat I E N T S T R E At E mentioning
confidence: 99%